An investigation into the effect of surface integrity on the fatigue failure of AISI 4340 steel in different drilling strategies. (January 2019) - Rasti, Amir; Sadeghi, Mohammad Hossein; Farshi, Sina Sabbaghi
Abstract: DTH bits often fail because of fatigue fracture at the machined holes location. In order to understand the failure mechanism and improve the fatigue life of drill bits, the effects of drilling parameters and surface integrity on fatigue life of the AISI 4340 holed samples have been investigated. Three hole making strategies, including drilling with and without pre-drill and helical milling were utilized and compared. Results showed that the fatigue life increased by raising the cutting speed and decreasing the feed rate. The only exception was the two-fold variations of fatigue life versus feed rate when using pre-drill. Besides, the higher fatigue life was achieved in drilling with pre-drill, helical milling and conventional drilling, respectively. In fact, using pre-drill resulted in a better surface integrity compared to conventional drilling and higher work hardening relative to helical milling. Also, images of fractured surfaces represented radiation of discontinuous fatigue cracks from an initiation site near the hole middle plane. Highlights: Effects of drilling parameters and surface integrity on fatigue life have been investigated in hole making strategies. Higher surface integrity parameters are attained in drilling, drilling with pre-drill and helical milling, respectively. Higher fatigue life is achieved in drilling with pre-drill, helical milling and drilling, respectively. Using pre-drill results in a smoother surface compared to drilling and higher work hardening relative to helical milling.